Effective Parameters on Performance of Multipressure Combined Cycle Power Plants - M. M., Rahman; Thamir K., Ibrahim (Hindawi Publishing Corporation, 2014)
A parametric analysis is performed for numerous configurations of a combined-cycle gas turbine (CCGT) power plant, including single-pressure, double-pressure, triple-pressure, triple-pressure with reheat, and supplementary triple-pressure with reheat. The compression ratio of the gas turbine and the steam pressure of the steam turbine are taken as design parameters. The thermodynamic model was developed based on an existing MARAFIQ CCGT power plant and performance model code developed using the THERMOFLEX software. The results show that the highest overall power and thermal efficiency occurs for the supplementary triple pressure with reheat CCGT configuration. The overall efficiency increases with an increase of the compression ratio to 18–20, depending on the configuration of the CCGT, then decreases with any further increase of compression ratio. The triple-pressure with reheat CCGT configuration has the highest overall thermal efficiency. The specific fuel consumption decreases with an increase of the compression ratio to 18–20, and the triple-pressure with reheat CCGT has the lowest specific fuel consumption. The simulation model gives good results compared with the MARAFIQ CCGT power plant. Consequently, it can be stated that the compression ratio and steam pressure strongly influence the overall power and thermal efficiency of CCGTs.